Legal Counseling on the Determination of Coastal Area Rehabilitation Regulations and Environmental Responsibility - Tuhulele, Popi; Waas, Armelia Febriyanti (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The importance of community service activities is that the academic world is obliged to provide education and legal understanding for the community. As a form of protection for citizens from all forms of discriminatory acts, it is the implementation of constitutional rights.Purposes of The Devotion: Coastal communities, especially those in Kampung Seri, Negeri Urimessing, understand the authority of institutions in regulating the determination of coastal area rehabilitation regulations and responsibility for the environment as well as to obtain suggestions and inputs from coastal communities directly that can be studied by the Government. Method of The Devotion: Community service activities through legal counseling are considered important to be carried out in order to provide legal understanding that legal tools in the form of regulations are very important to be held to ensure the protection of the environment and as a legal basis in rehabilitating areas that have experienced environmental damage, especially in coastal areas.Results Main Findings of the Devotion: Through this Community Service program, it is how to build legal awareness related to the importance of establishing regulations related to the rehabilitation of coastal areas as an effort to restore the environment as the responsibility of the community and the government. This activity involves the community and the government in the Urimessing Country, Ambon City. The problems examined in Community Service activities are closely related to the problems faced by the community today, with this community service activity it is expected to provide legal awareness and solutions about the importance of legal tools that function as an initial protection for the community and its environment to ensure sustainable environmental benefits.